Aza‐BODIPY Derivatives Containing BF(CN) and B(CN)2 Moieties1. Issue 2 (12th December 2016) - Li, Tian‐yi; Ma, Zaifei; Qiao, Zhi; Körner, Christian; Vandewal, Koen; Zeika, Olaf; Leo, Karl
Abstract: Two novel aza‐BODIPY derivatives are synthesized, with the fluorine atoms in the BF2 moiety replaced by cyano groups. The introduction of cyano groups changes the phenyl substituents on the 3, 5 positions from parallel to antiparallel. The HOMO/LUMO energy levels are stabilized gradually upon increasing the number of cyano groups, and the photophysical properties show corresponding shifts. With high thermal stability, the derivatives can be purified by sublimation and used to prepare vacuum‐deposited thin films. This research extends the aza‐BODIPY family with cyano‐substituted derivatives. Abstract : Novel aza‐BODIPY derivatives : The fluorine atoms in the BF2 moiety in aza‐BODIPY dyes are for the first time replaced by one or two cyano groups (see figure), and two corresponding derivatives are achieved with the presence of different Lewis acids. The outstanding photophysical properties are retained in the derivatives. The frontier molecular orbital energy levels can be tuned with different numbers of cyano groups.